Mengembangkan Keterampilan Digital dalam Pendidikan Kejuruan Melalui Inovasi Kurikulum dan Pembelajaran Berbasis Teknologi - Perez, Carlos; Khasanah, Fata Nidaul; Ismiyanti, Yulina; Herman, Herman (Jurnal MENTARI: Manajemen, Pendidikan dan Teknologi Informasi, 2025)
The rapid industrial transformation driven by digitalization has highlighted the significance of vocational education in equipping students with relevant digital competencies. This study aims to explore how innovations in curriculum and technology-based learning can effectively develop digital skills among vocational education students, in line with the evolving demands of the modern workforce. Utilizing a qualitative case study method, the research was conducted in three vocational high schools in Indonesia, with data collected through interviews with educators, classroom observations, and analysis of the implemented curriculum documents. The primary focus of the study is to identify curriculum elements and pedagogical strategies that integrate digital literacy, automation, and Industry 4.0 tools into the learning process. The findings indicate that the implementation of modular digital content, project based learning, and blended learning platforms significantly enhances student engagement and competencies in digital areas such as data analysis, cloud computing, and digital collaboration. Additionally, institutional support, teachers digital readiness, and partnerships with industry are key factors in the sustainable integration of technology in vocational education. In conclusion, this research emphasizes that systematic curriculum reform, supported by strategic utilization of educational technology, not only improves digital skill mastery but also fosters adaptive attitudes and lifelong learning, thereby preparing vocational students to face a dynamic and technology-driven job market in the future.